Estudo de longa duração da distribuição espaço-temporal de nutrientes no rio do Monjolinho, São Carlos - São Paulo - Barrenha, Pedro Ivo Isá (Universidade Federal de São Carlos, 2015)
In this study, it was made the determination of nutrients (in the forms of orthophosphate, total phosphorus, nitrogen series, total nitrogen and total dissolved carbon) and physicochemical variables in surface waters and sediment of the Monjolinho River, in São Carlos – SP, Brazil. Six sampling points were selected (stream head waters, at the UFSCar, upstream to the effluent treatment plant, Água Quente Stream, downstream to the effluent treatment plant and near the river mouth), in which were possible to observe a tendency of increase of the impact suffered by the aquatic body along its course. These tendencies were more pronounced from the region of the upstream to the effluent treatment plant (where the urban superficial flow carries the wastes to the river) to the region downstream to the effluent treatment plant. At the Água Quente Stream and downstream to the effluent treatment plant points, the input of non-treated and treated wastewaters are responsible for the substantial increase in the concentration of nutrients and alterations in physicochemical variables that reflects the impact suffered by the river. It was also noticed a seasonal tendency of variation in the measured values in agreement to the pluviometric indices of the studied region. Evaluating the Redfield ratio values, it is postulated that the phosphorus is the limiting nutrient in this ecosystem. The Tukey tests, HCA and PCA applied to the results allowed to separate sampling points into different groups according to the data obtained for each chemical analysis, showing that there is a tendency of increase on the impact suffered by the water body from its head waters to the sampling point downstream of the effluent treatment plant.
Long-term study of the spatio-temporal distribution of nutrients in the Monjolinho river, São Carlos – São Paulo
Keywords: Química ambiental; Fósforo; Nitrogênio; Eutrofização; Águas superficiais; Sedimentos; Phosphorus; Nitrogen; Eutrophication; Surface waters; Sediment; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL